ИЗБЫТОЧНАЯ ПАРАДИГМА «ГОДЫ-ЛЕТА» В АСПЕКТЕ ОНТОГНОСЕОЛОГИИ - Сенкевич, Василий (Conversatoria Litteraria, 2020)
Antithesis of juvenility and senility is examined in connection with grammatical presentation of redundant paradigm «years – times». In the context of understanding of the meaning of existence and the idea of being the thesis of not an existential nature of senility is formulated. In ontognoseological aspect the contraposition of concepts of «reality» and «actuality» becomes meaningful.